PEMIMPIN INFORMAL DAN DINAMIKA SOSIAL (Studi Kasus Lima tokoh Di Desa Allu Taroawang Kecamatan Batang Kabupaten Jeneponto) - Abd. Wahidin; Asmaun Azis; Dwia A. Tina P (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
The substance of this research was to find out, to describe, to provide information about roles and statuses by informal leaders in Allu Tarowang village as well as its relationship with social dynamics that occurred. Informal leaders have roles and statuses that is important and strategic in the dynamics of development. This statement was the research result that has been done with use three variabels: identifying the process how to be an informal leader, identifying the ability of informal leaders how to conduct social change and how to problem solving strategies in the dynamics of development. The method which used in this research is descriptive research with case study while techniques of the data collection uses indepth interview and observation afterwards data analysis is qualitative. The research result, in identifying the process how to be an informal leader was obtained two-factors: social needs and social status factors. However, it is reviewed from nature of the informal leaders was included traditional leader type. In identifying the ability of informal leaders how to conduct social change were influenced by attitudes and behavior, alignment of instruction and expectations of the community, means and approaches. And last, In identifying the ability of informal leaders how to problem solving strategies in the dynamics of development were divided three stages, with regards to: (1) looking at the condition and situation of problem, (2) knowing the source of the problem, and (3) finding out the alternative of the solution for the problem. Based on the description above, this researh shows an informal leader as a respected person and a role models in society. other than, they have roles for motivating, mediating and catalysting in the dynamics of development.